ANTIBACTERIAL ACTIVITY OF MOSS ENTODON MYURUS (HOOK) HAMP. AGAINST SOME PATHOGENIC BACTERIA - PREM KUMAR; B. L. CHAUDHARY (The Bioscan, 2010)
The crude extract with solvents such as ethanol, petroleum ether, acetone and benzene of Entodon myurus were tested for antibacterial activity against some pathogenic bacteria by agar well diffusion method. All the plant extracts showed activity against the tested microorganisms. Maximum antibacterial activity showed by acetone (29 mm) and methanol (29 mm) extract against Enterobacter aerogenes while minimum antibacterial activity showed by acetone extract(20 mm) against klebsiella pneumoniae.